Composition of Magma and Characteristics of the Hydrothermal System of Newberry Volcano, Oregon, From Magnetotellurics. (2nd March 2020) - Bowles‐Martinez, E.; Schultz, A.
Abstract: We use 3‐D magnetotellurics to improve our understanding of the structure and magma composition of Newberry Volcano in Oregon, USA. Newberry is a broad shield volcano with a summit caldera and strongly bimodal magmatism. Newberry has long been the subject of geothermal exploration research, but that work has focused on the volcano's west flank, leaving the caldera largely unstudied with geophysical methods until recently. Our modeling shows a relatively resistive magma reservoir of approximately 50 Ωm. Our work builds upon recent seismic models and petrological analysis to interpret Newberry's magma reservoir as a dry rhyolite with 8–11% partial melt, which matches the seismically determined melt fraction. Finding the conditions within the magma reservoir that allow the resistivity and seismic analysis to come to the same melt fraction helps us narrow down the magma temperature and composition. From this we infer a dry rhyolitic magma at 850 °C. We also image a prominent vertical conductive anomaly along the south rim below the vent that produced the most recent eruption. The anomaly extends from magma reservoir depths of 3 km to 1 km below the surface where it disperses into the caldera fill. We interpret this as the main conduit for magmatic fluids to reach Newberry's hydrothermal system. Other features that our model shows include higher conductivity along the caldera rim and a resistive older pluton on the west flank. Plain Language Summary: By studying the electrical conductivity of rocks and groundwater on Newberry Volcano near Bend, Oregon, USA, we show that its magma chamber has a very low water content and is very high in silica. This combination makes it invisible to our sensors, and the magma's invisibility allows us to infer its composition by comparing it with the characteristics observed with other geophysical and geological methods. By combining these methods in our interpretation, we determine that it contains no more than about 11% partial melt. Because our method is very sensitive to the presence of conductive groundwater, we are also able to see a vertical feature that we interpret as a pipe‐like structure carrying water upward from the magma chamber to shallow depths within the caldera. This structure appears to follow the path taken by the most recent eruption. We also image a large resistive structure beneath the west flank that we interpret as a granite‐like rock that has solidified from an ancient magma chamber but still has enough heat to be an attractive target for geothermal energy production. Key Points: Three‐dimensional magnetotelluric modeling shows that Newberry's magma chamber is unusually resistive, making it invisible to magnetotellurics Constraints from previous seismic models and geochemical analysis of Newberry rhyolites and basaltic andesites suggest a dry rhyolitic 8–11% partial melt A vertical conductor shows a fluid conduit from the magma chamber to the caldera fill beneath the most recent eruption